Attitude towards online shopping during pandemics: Do gender, social factors and platform quality matter? - Nada Mallah Boustani; May Merhej Sayegh; Zaher Boustany (Journal of Risk and Financial Management, 2022)
Because of the advancement of electronic commerce, online shopping has emerged, merging commercial and social activities and enhancing the social presence and value of the online environment. To improve the understanding of the changes in the consumer behavior during the COVID-19 pandemic, this study proposes a set of characteristics connected to the social side of online shopping and their influence on client purchasing attitude in addition to the quality of the platforms that are being used (service quality, system quality and information quality). For this matter, a survey of 289 Lebanese people was circulated in 2021 and a quantitative method was used to answer three research questions. Types of goods purchased and frequency of buying on-line were tested to check the presence of any gender differences, in addition to the relationship between the variables studied in the model. According to the research, social presence, social value, and tendency to compare products on different shopping platforms all have a significant correlation with the attitude towards online shopping, where the system quality was the least significant. When it comes to purchasing frequency and product types, the data gathered imply that gender disparities are considerable. This study does not consider the consumer's living environment or whether there are any age differences between the generations shopping online.
Keywords: M30; D91; O30; 650; attitude; consumer behavior; online shopping; pandemic; quality information; quality service; quality system; social presence; social value; tendency to compare